HISTORICAL AND SOCIAL PERSPECTIVES OF BLYTON’S THE FAMOUS FIVE - Fauziah, Nurul; Harits, Imron Wakhid (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2022)
This article examines the historical and social perspectives in children literature of three series of Blyton’s The Famous Five. The objective of this study is, to explain the historical context and social perspectives of the three series novel of The Famous Five. This study used qualitative method to collect, select and analyze the data. The data of this study is three series of novel The Famous Five by Enid Blyton. This study used document analysis as the process of collecting data in this research. The writer collected the data using some notes and online news as the instrument to get the data. The theory used in this study is historical and social approaches in children literature by Jack Zipes. The study found some historical aspects and social elements in the novel. The result of this study showed that (1) there are twelve historical aspects dealing with place, event, and artifact. (2) there are four social elements dealing with economic condition, gender equality, tradition, and culture. The historical aspects and social elements of Blyton’s The Famous Five are depicted in the form of conversation and paragraphs. Based on the result of this study, the writer concludes that Blyton’s background influences the process of the historical aspects and social elements which are depicted in the three series of Blyton’s The Famous Five.